Medical assistance in dying and the trust of faith. Issue 4 (19th January 2023) - Merrill Childs, James
Abstract: The ethical discussion of end‐of‐life decisions has been with us for some time. This article focuses specifically on medically assisted dying. Representative secular, professional, and faith‐based ethical arguments for and against it are briefly reviewed. With respect for the contributions of that ethical discourse, the article sees the decision for aid in dying as a spiritual matter of the trust and freedom of faith in the loving, intimate presence of the Triune God with us in the incarnate Christ, and his union with the Father and the Spirit.